2017
DOI: 10.1016/j.pbb.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent access to a nutritionally complete high-fat diet attenuates alcohol drinking in rats

Abstract: Binge eating disorder and alcohol use disorder (AUD) frequently co-occur in the presence of other psychiatric conditions. Data suggest that binge eating engages similar behavioral and neurochemical processes common to AUD, which might contribute to the etiology or maintenance of alcoholism. However, it is unclear how binge feeding behavior and alcohol intake interact to promote initiation or maintenance of AUD. We investigated the impact of binge-like feeding on alcohol intake and anxiety-like behavior in male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
34
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 83 publications
(103 reference statements)
10
34
2
Order By: Relevance
“…Our finding that ad libitum HFD access decreases ad libitum EtOH intake (UAE+HFD group) is a common finding in the literature in both male and female rodents (Feng et al, 2012;Gelineau et al, 2017;Sirohi et al, 2017aSirohi et al, , 2017b. This may be due to a number of factors.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Our finding that ad libitum HFD access decreases ad libitum EtOH intake (UAE+HFD group) is a common finding in the literature in both male and female rodents (Feng et al, 2012;Gelineau et al, 2017;Sirohi et al, 2017aSirohi et al, , 2017b. This may be due to a number of factors.…”
Section: Discussionsupporting
confidence: 69%
“…A similar positive relationship for EtOH-induced increases in HFD intake has been shown in some animal models (Barson et al, 2009). While the inverse relationship of HFD exposure stimulating EtOH intake has also been suggested in some animal models (Carrillo et al, 2004), the majority of findings indicate that HFD exposure decreases EtOH consumption (Feng et al, 2012;Gelineau et al, 2017;Sirohi et al, 2017aSirohi et al, , 2017b. The majority of these previous studies, however, have examined EtOH intake in the face of HFD access without specific focus on metabolic function, or examined metabolic effects of EtOH and HFD without taking intake behaviors into account.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…For example, a recent study found that i.c.v.‐injected ghrelin shifts diet preference, increasing RC intake and reducing HF intake, in rats exposed to a 2‐week binge eating protocol with simultaneous access to both diets . Also, it was shown that rats intermittently and time‐limited fed with different palatable diets for several weeks displayed higher plasma ghrelin levels before each binge eating event . In particular, one study found that increments of plasma ghrelin levels positively correlated with food anticipatory activity and that a GHSR antagonist decreased such behaviour, whereas another study showed that blockade of plasma ghrelin increments attenuated the magnitude of binge‐like HF intake .…”
Section: Discussionmentioning
confidence: 99%
“…58 Also, it was shown that rats intermittently and time-limited fed with different palatable diets for several weeks displayed higher plasma ghrelin levels before each binge eating event. [59][60][61][62][63] In particular, one study found that increments of plasma ghrelin levels positively correlated with food anticipatory activity and that a GHSR antagonist decreased such behaviour, 60 whereas another study showed that blockade of plasma ghrelin increments attenuated the magnitude of binge-like HF intake. 63 Moreover, two studies found that mice or rats intermittently and time-limited fed with a palatable diet over several weeks displayed a reduction of plasma ghrelin levels immediately after the last binge eating event.…”
Section: Discussionmentioning
confidence: 99%